Comparative study between pectoralis and leg muscles in flying and running/walking birds in two different ages ( post-hatching and mature ) - H.A-ameer, Taghreed; M.A-kareem, Hashim (Al-Qadisiyah Journal of Pure Science, 2018)
This study deals with a number of skeletal muscles in two types of birds ; flying (pigeon ) and running (chicken ) types . The total number of the studied birds was 30; 15 were chicken and 15 were pigeons. Some of the physiological and histological characteristics of the muscle fibers (red, white, and intermediate ), the percentage of fibers diameter in the studied muscles, and the change noted in the muscle weight with advancing age had been calculated. The species of the chicken in this study was Gallusdomesticus , while the species of the pigeons was Columbia livia. The muscles that is used in the study were : pectoralis muscle , femortibialis, triceps, biceps brachii, extensor carpi radialis muscle, and gastrocnemius muscles in two age groups of birds; ( 3-6 ) and ( 6-12 ) months . The results had shown that the skeletal muscles in birds consist of heterogenous mixture of the three types of muscle fibers ( red, white, and intermediate ) and that the size of the white muscle fibers in pectoralis muscle of both types ( chicken and pigeons ) and in both age groups used in this study was about 75% of the total size of the muscle i.e. the white fibers are the predominant type of fibers in this muscle, while the red fibers forms about 25% of the total size.